EFEKTIVITAS PENYULUHAN KESEHATAN TENTANG ANEMIA TERHADAP PENGETAHUAN IBU HAMIL PASCA KRISIS KESEHATAN DI PUSKESMAS PANAMBUNGAN - Puspita, Winda Dwi; Purnamasari, Dian; W, Ikrawanty Ayu; AR, Putra Az-Zahra (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan Pelamonia, 2025)
Background Anemia in pregnant women is strongly related to mortality and morbidity in mothers and babies, including the risk of miscarriage, stillbirth, prematurity, and low birth weight. The purpose of the study is to determine the effectiveness of health counseling and increase the knowledge of pregnant women about anemia in pregnancy. Methods This study uses quantitative research with the